A constructive proof of the ordinal efficiency welfare theorem. - Manea, Mihai (Journal of Economic Theory, 2008)
We provide a non-geometric constructive short proof of the ordinal efficiency welfare theorem. Copyright (c) 2008 Elsevier Inc.